Effect of gasoline vaporizer tube (GVT) with magnetic field on spark-ignition engine: Investigation, discussion, and opinion - Rani Anggrainy; Wegie Ruslan; Dede L. Zariatin; Ramón A. Gilart; Thaer Syam (Mechanical Engineering for Society and Industry, 2022)
Applying magnetic fields to improve the arrangement of hydrocarbon molecules in fuel lines have been continuously studied in recent decades. However, scientific reports regarding the application of a magnetic field integrated with a gasoline vaporizer tube (GVT) on engine performance have not been widely discussed. Therefore, this article presents an investigation of the application of GVT with magnetic field on a single cylinder gasoline engine with three different fuel qualities, including RON88, RON92, and RON98. Torque, power, emissions and fuel consumption have been tested for scientific opinion. The results of our present investigation seem to confirm the claims of GVT inventors, where GVT increases engine torque and power, reduces CO and HC content in exhaust gases, and reduces fuel consumption. However, without considering the supply of gasoline and air from the GVT to the engine is an unfair analysis. In fact, although the established theories reveal the benefits of applying a magnetic field to the fuel line, in this case, only a small part of the fuel is induced by the magnetic field, outside the main line from the tank to the injectors. Finally, the results of this investigation provide new insights for potential users of GVT, which is currently commercially available.